PENYULUHAN DAMPAK POLUSI UDARA DARI AKTIVITAS PRODUKSI KERUPUK TAHU DI DESA TLASIH, TULANGAN - SIDOARJO - Tamyiz, Muchammad; Saputro, Arief; Mustaqim, M.; Hamidah, Zumrotul; Ayubi, Anis Al (Jurnal Abdi Insani, 2025)
Air pollution has increasingly become a serious global issue, driven by the rise of industrial activities, transportation, and fossil fuel use. Pollutants such as fine particles, sulfur dioxide (SO₂), nitrogen oxides (NOx), carbon monoxide (CO), and volatile organic compounds (VOCs) pose threats to human health and environmental sustainability. Tlasih Village in Sidoarjo, East Java, known as a center for the cracker industry, has the potential to contribute to air pollution due to the use of non-environmentally friendly fuels in production processes. This study aims to raise awareness among the residents of Tlasih about the impacts of air pollution through direct socialization activities conducted with cracker producers on July 26, 2024. The method involved presenting material on the effects of air pollution on health and the environment and introducing alternative, cleaner fuels. Survey results indicated that the majority of respondents already had a basic awareness of air pollution, with 17.5% demonstrating in-depth understanding and 65% showing moderate awareness of its impacts. However, only a small number actively participated in socialization activities or pollution reduction efforts. Further socialization is necessary to shift mindsets and enhance active community involvement. This study suggests that environmental education campaigns should be intensified, particularly those focusing on practical solutions to reduce pollution, to foster a healthier environment in Tlasih Village and its surroundings.